2023
DOI: 10.1093/rheumatology/keac713
|View full text |Cite
|
Sign up to set email alerts
|

An international survey of current management practices for polymyalgia rheumatica by general practitioners and rheumatologists

Abstract: Objectives To explore current management practices for polymyalgia rheumatica (PMR) by general practitioners (GPs) and rheumatologists including implications for clinical trial recruitment. Methods An English language questionnaire was constructed by a working group of rheumatologists and GPs from 6 countries. The questionnaire focused on: 1: Respondent characteristics, 2: Referral practices, 3: Treatment with glucocorticoids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…Although glucocorticoid minimization has been the main driver of steroid-sparing agent use in patients with PMR, achievement of remission and potentially drug-free remission are targets that should be considered and that studies such as the methotrexate trials and the recent PMR glucocorticoid sparing (PMR-SPARE) trial suggest (8,18). However, current practices in the referral of patients with PMR to rheumatology (ie, low percentage of referrals, delayed timing of referrals, cumulative glucocorticoid use at time of referral) need to be examined to better understand the benefits of additional agents to minimize long-term glucocorticoid toxicities (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although glucocorticoid minimization has been the main driver of steroid-sparing agent use in patients with PMR, achievement of remission and potentially drug-free remission are targets that should be considered and that studies such as the methotrexate trials and the recent PMR glucocorticoid sparing (PMR-SPARE) trial suggest (8,18). However, current practices in the referral of patients with PMR to rheumatology (ie, low percentage of referrals, delayed timing of referrals, cumulative glucocorticoid use at time of referral) need to be examined to better understand the benefits of additional agents to minimize long-term glucocorticoid toxicities (7).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the relatively high prevalence of PMR, there are little data on the use of steroid-sparing agents for PMR (3). A lack of large observational cohort studies, clinical trials, and the burden of most care for patients with PMR occurring in the primary care setting are potential contributing factors (7). Recently, a small number of randomized, placebo-controlled clinical trials have shown the efficacy (ie, disease remission and steroid-sparing effect) of interleukin (IL)-6 inhibitors (tocilizumab and sarilumab) and rituximab for PMR (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…In the first scenario, patients are usually managed in primary care or rheumatology out-of-hospital settings,12 13 whereas the presence of systemic manifestations may lead to hospitalisation 14. An international online survey of 394 GPs and 937 rheumatologists showed that only 25% of patients with suspected PMR are referred from primary care to rheumatologists, with substantial variation between countries, ranging from 10% in the UK and the Netherlands to 60% in Italy and Romania, and up to 100% in Colombia (with wide variation in the percentage of referral also within countries) 15. A median of 50% (IQR 15%–75%) of patients were seen by a rheumatologist after starting treatment in the primary care setting.…”
mentioning
confidence: 99%
“…Considerable differences are evident in the diagnostic approach taken by GPs and rheumatologists. More than 15% of GPs do not always request C reactive protein in patients with suspected PMR, more than 40% never or rarely check the presence of anticitrullinated protein antibodies, and about two-thirds never or rarely ask for any imaging examination 15. The approach to treatment by GPs and rheumatologists is also discrepant.…”
mentioning
confidence: 99%
See 1 more Smart Citation